The LOFAR view of cosmic magnetism. Issue 6 (1st July 2013) - Beck, R.; Anderson, J.; Heald, G.; Horneffer, A.; Iacobelli, M.; Köhler, J.; Mulcahy, D.; Pizzo, R.; Scaife, A.; Wucknitz, O.; the team of the LOFAR Magnetism Key Science Project,
Abstract: The origin of magnetic fields in the Universe is an open problem in astro‐physics and fundamental physics. Polarization observations with the forthcoming large radio telescopes will open a new era in the observation of magnetic fields and should help to understand their origin. At low frequencies, LOFAR (10–240 MHz) will allow us to map the structure of weak magnetic fields in the outer regions and halos of galaxies, in galaxy clusters and in the Milky Way via their synchrotron emission. Even weaker magnetic fields can be measured at low frequencies with help of Faraday rotation measures. A detailed view of the magnetic fields in the local Milky Way will be derived by Faraday rotation measures from pulsars. First promising images with LOFAR have been obtained for the Crab pulsar‐wind nebula, the spiral galaxy M 51, the radio galaxy M 87 and the galaxy clusters A 2255 and A 2256. With help of the polarimetric technique of "Rotation Measure Synthesis", diffuse polarized emission has been detected from a magnetic bubble in the local Milky Way. Polarized emission and rotation measures were measured for more than 20 pulsars so far. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)